Subproblem learning and reversal of a multidimensional visual cue in a lizard: evidence for behavioural flexibility?. (October 2018) - Szabo, Birgit; Noble, Daniel W.A.; Byrne, Richard W.; Tait, David S.; Whiting, Martin J.
Abstract : Behavioural flexibility, the ability to adjust behaviour to environmental change by adapting existing skills to novel situations, is key to coping with, for example, complex social interactions, seasonal changes in food availability or detecting predators. We tested the tree skink, Egernia striolata, a family-living skink from eastern Australia, in a set-shifting paradigm of eight colour/shape discriminations including reversals, an intradimensional acquisition of a new colour/shape and extradimensional shift from colour to shape (and vice versa). Skinks could learn to discriminate between colour/shape pairs and reverse this initial stimulus–reward association; however, they showed no significant decrease in the probability of making a correct choice in the extradimensional shift suggesting that they did not form an attentional set. Subjects appear to have learnt each stage as a new problem instead of generalizing stimuli into specific dimensions (set formation). In conclusion, tree skinks solved a discrimination reversal by focusing their attention towards visual stimuli and flexibly adjusting their choice behaviour accordingly. These lizards learned to use multidimensional visual stimuli to find a food reward but did not generalize stimuli into dimensions. Furthermore, this study is the first to test for set shifting in a lizard species and thereby allows us to extend set-shifting theory to a new taxon for comparison with primates, rodents, a bird and a turtle. Highlights: Lizards discriminated between four pairs of visual stimuli (shapes and colours). Animals showed behavioural flexibility through reversal learning. The results do not support the formation of an attentional set. Lizards were able to learn during the shift stage.